Partição da digestão e escape ruminal de ácidos graxos de cadeia longa em novilhos suplementados com óleo de soja, vitamina E e selênio orgânico - Ferreira, Adriano Vinícius de Paiva (2016)
In this work, the consumption, the digestibility aimed to value in the total digestive treatment, you chew the parameters, the degradabilidade of the MS and the leak ruminal of AGCL in young bulls supplemented with 6 % of oil of soy (THEM), organic selenium (If) and vitamin E (V). Five animals were used canulados in the rumen, distributed in a delineation in Latin square 5×5. The diets were formulated for profit of 1,3 kg / day weight and the levels of suplementação of V and 1.500 went away, respectively, Ouch / day and 5 g/dia was seeing cânularuminal. The treatments were: SLA (without lipídeo additional); (6 % of THEM); OS+V (6 % of THEM + V); OS+Se (6 % of THEM + If); OS+Se+V (6 % of THEM + If + V). The suplementação with THEM reduced the consumption of MS (P=0,02), MS regarding the lively weight (g/kg PV; P <0,01), MILLSTONE (P=0,05), PB (P=0,02), FDN (P=0,01), ashes (P=0,05) and CNF (P <0,01). However, bigger consumption of EE was checked for these diets (P <0,01). The diets reduced THEM the total digestibility of the MS (P=0,05), MILLSTONE (P=0,05), CNF (P=0,04) and total digestibility of the FDN (P <0,01). And it increased the total digestibility of the EE (P <0,01;) . The fraction B and the potential degradabilidade of the ensilage of corn and of the grass napier they were bigger for the diet SLA regarding other diets (P≤0,01). The middle values of pH ruminal tended to increase with the suplementação of lipídeos, (P=0,06), and the very values were bigger for these diets. Meantime, the pH fell after the food of the animals (P <0,01). The diets did not affect the efficiency of synthesis of microbial protein, however the addition of oil reduced the excretion of N microbial (P=0,01). The concentration of N-NH3 was not affected by the experimental diets, however it was influenced by the time after the morning food of the animals. The suplementação with lipídeo had a tendency to reduce the relation acetato:proprionato (P=0,08), and it If in the diets with oil it increased the concentrations of main AGVs in the rumen. The diets reduced THEM the counting of protozoários totals (p <0,01), and it altered most of the AGCL that passed of the rumen for the omaso, reducing the acids C12; 0, C14:0, C15:0, C16:0 (P <0,01), C17:0 (P=0,02), C18:0 (P <0,01), C18:2 cis 9,12 (P=0,01), increasing the C18:1 trans-9 (P=0,02) and the C18:2 trans-10 cis-12 (P <0,01). The oil addition reduced the concentration of AGPI regarding the diet SLA, however, the suplementação of one tended to increase the concentration of these (P=0,07) and of the acid linoleico (C18:2 cis 9,12; P=0,07).